1987
DOI: 10.1099/0022-1317-68-4-995
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular RNAs of the Feline Infectious Peritonitis Coronavirus Strain 79-1146

Abstract: SUMMARYIn Fells catus whole foetus D cells infected with feline infectious peritonitis virus (FIPV), strain 79-1146, six virus-specific, poly(A)-containing RNA species of about 20, 9.6, 5.2, 3.8, 2.8 and 1.6 kb were found. By translation in vitro the 3.8 and 2-8 kb RNAs were shown to encode the 25K envelope protein and the 45K nucleocapsid protein, respectively. The partial map of the FIPV genome was compared with genomic maps of porcine, murine and avian coronaviruses. Differences in these maps suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Assuming an RNA leader sequence of 60-70 nucleotides (Spaan et al, 1983;Lai eta/., 1984;Brown eta/., 1984) and a poly(A) tail of about 100 nucleotides we arrive at a predicted length of approximately 1400 nucleotides. Previously, RNA 6 was estimated to be 1600 nucleotides (de Groot et aL, 1987a). By using gels with a better resolution in this MW range, we have now measured a length of about 1450 nucle0tides (not shown).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Assuming an RNA leader sequence of 60-70 nucleotides (Spaan et al, 1983;Lai eta/., 1984;Brown eta/., 1984) and a poly(A) tail of about 100 nucleotides we arrive at a predicted length of approximately 1400 nucleotides. Previously, RNA 6 was estimated to be 1600 nucleotides (de Groot et aL, 1987a). By using gels with a better resolution in this MW range, we have now measured a length of about 1450 nucle0tides (not shown).…”
Section: Resultsmentioning
confidence: 60%
“…Differences in the mRNA sets of TGEV Purdue and FIPV 79-1146 indicated the presence of large insertions at the 3' end of the FIPV genome (de Groot et al, 1987a). We have characterized these insertions by sequence analysis of recombinants which had been isolated from a FIPV-specific cDNA library by hybridization with the smallest FIPV mRNA (RNA 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous report (de Groot et al, 1987a) we have shown that in FIPV-infected cells six virus-specific RNAs are produced with sizes ranging from 1.6 to at least 20 kb. Data on the RNAs and their coding assignment are summarized in Fig.…”
Section: Introductionmentioning
confidence: 93%